Four-year review of safe and effective procedural sedation in neonates and young infants - Cui, Yu; Tang, Min; Mu, Qixia; Wu, Qunying; Kang, Lu; Chen, Qin; He, Yani (Frontiers in Pharmacology, 2024)
Objectives Newborns and small infants are unable to cooperate actively during diagnostic procedures; therefore, sedation is often employee to maintain immobilization and obtain high-quality images. However, these procedures are often indicated in sick, vulnerable, or hemodynamically unstable neonates and young infants, which raises the associated risks of sedation. This study summarizes our 4-year of experience with safe and effective procedural sedation in this vulnerable population. Study design This retrospective study analyzed data on neonates and young infants who underwent non-painful diagnostic procedures from December 2019 to November 2023. Patients were categorized into the neonate (aged≦ 28 days) and the young infant (29 days ≦ aged ≦ 90 days) groups. Results Non-pharmacological strategies, including sleeping naturally, swaddling/facilitated tucking, non-nutritive sucking, and skin-to-skin care, can achieve a success rate for sedation about 98.4%. In terms of pharmacological methods, our institution primarily utilizes chloral hydrate for procedural sedation in neonates and young infants undergoing non-painful diagnostic procedures. Midazolam serves as an alternative sedative. Chloral hydrate alone demonstrated a 92.5% success rate on the first attempt, compared to midazolam alone, with an 85.11% success rate. Neonates experienced a higher incidence of adverse events during sedation compared to young infants. Conclusion This study reviews our 4-year experience with procedural sedation in neonates and young infants. Chloral hydrate demonstrated a high degree of safety and efficacy in this population. However, supervision by skilled medical personnel and extended observation is required. In our institution, the experience with midazolam is limited in this population, and further research is warranted to establish its safety and efficacy. Non-pharmacological strategies can achieve an acceptable rate of sedation success, which can be used based on patient’s tolerance.